2006
DOI: 10.1051/0004-6361:20053158
|View full text |Cite
|
Sign up to set email alerts
|

Nearby AGN and their hosts in the near infrared

Abstract: We present near infrared ISAAC VLT observations of nine nearby (0.01 ≤ z ≤ 0.06) Active Galactic Nuclei selected from the Hamburg/ESO Survey and the Véron-Cetty & Véron catalog. Hydrogen recombination lines Paα and Brγ are observed in seven of the nine sources of which five show a broad component. In three sources, extended 1-0S(1) rotational-vibrational molecular hydrogen emission is detected. Stellar CO absorption is seen in four sources. In one of these objects, an upper limit of the central mass can be det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 41 publications
8
44
1
Order By: Relevance
“…Calibration was done using 2MASS magnitudes of foreground stars. For details on the data, see Fischer et al (2006).…”
Section: Isaac K-band Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Calibration was done using 2MASS magnitudes of foreground stars. For details on the data, see Fischer et al (2006).…”
Section: Isaac K-band Imagingmentioning
confidence: 99%
“…They find neutral atomic gas masses ranging from 1.1 × 10 9 M to 3.8 × 10 10 M but no strong correlation between gas mass and infrared emission that traces star formation and AGN activity. Fischer et al (2006) have observed nine galaxies from the sample with the near-infrared (NIR) spectrograph ISAAC (VLT) and find that the spectra show signs for both AGN activity and star formation. In our NIR study (Busch et al , 2014, we find that the LLQSOs do not follow published M BH −L bulge relations for inactive galaxies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This particular value was chosen to ensure the presence of the CO(2−0) band head in near-infrared (NIR) K-band spectra. This stellar absorption feature can be used to derive the stellar kinematics of the host galaxy or to analyze stellar populations (Gaffney et al 1995;Fischer et al 2006). These selection criteria result in a sample of 99 galaxies that we call the LLQSO sample throughout the text (for more information see Bertram et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several galaxies from the LLQSO sample have been observed in molecular gas (CO, Bertram et al 2007), atomic hydrogen (H , König et al 2009), and H 2 O-maser-emission (König et al 2012). Fischer et al (2006) studied nine galaxies in the NIR, focusing on spectroscopy.…”
Section: Introductionmentioning
confidence: 99%